eCM 2013
DOI: 10.22203/ecm.v025a10
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic medium is superior to growth factors in differentiation of human adipose stem cells towards bone-forming cells in 3D culture

Abstract: Human adipose stem cells (hASCs) have been recently used to treat bone defects in clinical practice. Yet there is a need for more optimal scaffolds and cost-effective approaches to induce osteogenic differentiation of hASCs. Therefore, we compared the efficiency of bone morphogenetic proteins (BMP-2 and BMP-7), vascular endothelial growth factor (VEGF), and osteogenic medium (OM) for the osteoinduction of hASCs in 3D culture. In addition, growth factors were tested in combination with OM. Commercially availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 69 publications
4
60
0
Order By: Relevance
“…On the other hand, TGF-β1 protects pre-osteocytes from apoptosis [63]. Similar results regarding the osteogenic medium were obtained by Tirkkonen et al [64] in an adipose stem cell osteogenic differentiation study that compared the efficiency of BMP-2 and BMP-7, VEGF and osteogenic medium. Stem cells were grown on commercially available bioactive glass scaffolds and biphasic granules.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, TGF-β1 protects pre-osteocytes from apoptosis [63]. Similar results regarding the osteogenic medium were obtained by Tirkkonen et al [64] in an adipose stem cell osteogenic differentiation study that compared the efficiency of BMP-2 and BMP-7, VEGF and osteogenic medium. Stem cells were grown on commercially available bioactive glass scaffolds and biphasic granules.…”
Section: Discussionsupporting
confidence: 61%
“…They did not find a benefit after the addition ofgrowth factors in comparison with plain osteogenic medium. Moreover, BMP-7 inhibited the proliferation and osteogenic differentiation of adipose stem cells [64]. The lack of improvement of the osteogenic differentiation of stem cells through the addition of BMP-2 or BMP-6 was also reported by other authors [65-67].…”
Section: Discussionmentioning
confidence: 80%
“…Contrary to the results of our study, D'Alimonte et al 42) showed that the addition of VEGF to the DSCs (10-40 ng/ml for 8-day dose-and timedependently) in osteogenic condition could enhance both osteogenesis and angiogenesis, while results of the current study disagreed with these fi ndings. The work of Tirkkonen et al 43) strongly agreed with our study as he confi rmed that using high dose of VEGF protein in free released did not enhance osteogenesis process due to diff erentiation of HASC by meant BMP-2 inhibition. BMP-2 is a growth factor that has a high ability to induce osteogenesis by inducing the signaling control osteogenesis 44) .…”
Section: Discussionsupporting
confidence: 90%
“…The current finding showed that only angiogenic enhances with VEGF-BCP combined group but not osteogenic. The work of Tirkkonen et al 31) strongly agreed with our study fi ndings as he confi rmed that VEGF did not enhance osteogenesis diff erentiation of human adipose stem cells (HASC) by meant BMP-2 inhibition. From this information, it is, therefore, clear that VEGF-BCP culture conditions had signifi cant eff ects in these experiments, but a defi nitive conclusion on angiogenesis and osteogenesis will need to be confi rmed by further studies.…”
Section: Discussionsupporting
confidence: 88%